HYDRUS 2D simulation of atrazine movement in tropical and temperate soil region under corn cultivation - Oliveira, Luciano Alves de (2019)
The crop productivity increase is often associated with an increase in the use of agricultural products, including herbicides. When these products are applied in an untidy way, leaching may occur and cause environmental contamination either at the soil or at the groundwater. Regarding herbicides, atrazine is widely used in Brazil and around the world. It is also considered as the main organic pollutant, and a potential contaminant of the water table. According to that, it is necessary to build a detailed knowledge about the dynamics of these molecules through the soil with the objective to better control the contamination risks. Thus, the main goal of this research was to simulate the atrazine\'s movement through both tropical and temperate soils under corn cultivation using HYDRUS package models, and to obtain equation parameters to transform electromagnetic induction (EMI) signal data in atrazine\'s movement parameters. Thus, the research was conducted in two different places: 1 - \"Luiz de Queiroz\" College of Agriculture (ESALQ/USP) at the Biosystems Engineering Department and at the Ecotoxicology Laboratory (CENA/USP) both in Piracicaba, SP (Brazil), and 2 - at the Meat Animal Research Center (MARC/ARS) from the United States Department of Agriculture (USDA) in Clay Center, NE (US). In Brazil, a corn crop using three treatments of atrazine was conducted in a greenhouse to obtain the herbicide concentration data from the soil solution. Then, soil samples were collected to run breakthrough curves (BTC) to obtain atrazine\'s movement parameters through STANMOD model. After that, atrazine\'s movement simulations were taken through the HYDRUS 2D model. In the end, statistical indexes were used to compare observed and modeled data aiming the evaluation of HYDRUS 2D model for the movement of atrazine. In US, EMI data were collected in a corn field before atrazine application. Then, soil samples from this field were collected for BTC\'s to obtain atrazine\'s movement parameters. After obtaining such parameters, models were generated correlating EMI signal data with atrazine\'s movement parameters. Subsequently, statistical comparison indexes were used to compare the actual data obtained with the data obtained by the new model generated. Finally, simulations of the movement of atrazine were made with the purpose of evaluating the contamination of the subsoil. In addition, maps with interpolated data were generated, facilitating the visualization of sites most susceptible to contamination. In Brazil, the atrazine\'s movement parameters were R = 1.604, β = 0.82 e ω = 2.5 h-1. Then, HYDRUS 2D simulations were precise (r = 0.9815) and accuracy (d = 0.9906) when the corn plant is not in the system. However, with the presence of the corn, HYDRUS 2D still predicted atrazine with precision (r = 0.8609) but the accuracy was low (d = 0.4449). In US, the atrazine\'s movement parameters were R = 7.45, β = 0.47, and ω = 5.56 h-1. Further, models using EMI signal data to predict atrazine\'s movement parameters were generated. The statistical indexes to these models were R2 = 0.9012, r = 0.9311, and d = 0.9589. Overall, HYDRUS 2D is a model to predict atrazine\'s movement through the soil. However, more researches need to be carried out considering the plant as part of the system and the parameters which account water and solutes absorption need to be improved. The EMI technique to obtain atrazine\'s movement parameters was also well succeeded. Thus, it should be broadly used to monitor atrazine and other contaminants.